Legal developments on the regulation of the affirmative action according Law 15/2022 - Sánchez-Girón Martínez, Beatriz (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
Positive action is part of the principle of equal opportunities, and their purpose is to avoid the situations of inequality which are source of discrimination. International and national law, has gradually been accepting its admission, and finally, not only regulates but also promotes them. Thanks to the case law the requirements of the measures of affirmative action are identified. In Spain, recently has entered into force the Law 15/2022, of July 12, about equality and non-discrimination, which culminates the process of transposition of the EU anti-discrimination Directives. Similarly, the latter also contains some references labour relations. The aim of this paper is to emphasize what are the requirements that every mea sure must satisfy to be considered a positive action, otherwise it would lack legitimacy. This will help to study what positive action measures are and what legal support they have had in our legal system, especially with regard to the workplace. Hereinafter, we will do, on the one hand, a comparison between the previous scenario, focused on the protection of people with disabilities and women, with collective bargaining as the leading role, and, on the other hand, we will assess the novelties introduced by this Law 15/2022. Although the social value of this law is undeniable because it extends the protection against discrimination to new subjects, we already anticipated that it does not stand out due to the novelties it brings to the legal regime of positive action.